Obstetrical and neonatal prognosis of a teenage primiparous pregnancy at the Zafisaona Gabriel Majunga university hospital center - Ratsiatosika, Tanjona A.; Rajaonarivony, Marie Valerie; Randriamahavonjy, Romuald; Rainibarijaona, Lantonirina; Fanomezantsoa, Jean Eustache; Rakotonirina, Martial; Randaoharison, Pierana Gabriel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Women's fertility is early and high in Madagascar. Through this study, want to know the obstetric and neonatal risks in teenage primiparous pregnancies. Methods: Carried out a retrospective comparative study of teenage primiparous pregnancies who gave birth beyond 22 weeks of amenorrhea (SA) at the Zafisaona Gabriel Mahajanga university hospital between the period from January 1 to March 31, 2015. The control group is made up of first-time mothers aged 20 to 35 who gave birth in the same center. Results: The mean age of the patients was 16.77±1.12 years. In 43.1% of cases, the pregnancy was poorly followed. 22.41% of new-borns to adolescent mothers were hypotrophic at birth. Teenage primiparous pregnancies had a risk of poor pregnancy monitoring compared to their elders (RR: 2.17, 95% CI [1.35-3.47]) and a risk of giving birth to a low birth weight child (RR: 2.1, 95% CI [1.05-4.44]). The risk of preeclampsia, death in utero, caesarean section, instrumental extraction was identical between the two groups. Regarding the outcome of newborns, the frequency of premature birth, early neonatal infection, neonatal asphyxia, early neonatal death was not significant. Conclusions: Apart from fetal hypotrophy, adolescent girls have the same maternal, fetal and neonatal prognosis as their elders.